Electrospinning of Bovine Split Hide Collagen and Collagen/Glycosaminoglycan for a Study of Stem Cell Adhesion and Proliferation on the Mats: Influence of Composition and Structural Morphology - Todorka G. Vladkova; Dilyana N. Gospodinova; Peter D. Dineff; Milena Keremidarska-Markova; Kamelia Hristova-Panusheva; Natalia Krasteva (Journal of Functional Biomaterials, 2025)
Electrospun collagen-based fibrous mats are of increasing interest for cell culture, regenerative medicine, and tissue engineering. The focus of this investigation is on the assessment of the electrospinning ability of bovine split hide collagen (BSHC), the effect of glycosaminoglycan (GAG) incorporation on the mats’ structural morphology, and the impact on the adhesion and proliferation of human adipose-derived mesenchymal stem cells (hAD-MSCs). Electrospun mats were prepared using benign and fluoroalcohol solutions of BSHC and BSHC/GAGs under varied operation conditions. SEM observations and analysis were employed to characterize the structural morphology of the mats. Several parameters were used to evaluate the hAD-MSC behavior: cytotoxicity, cell morphology, cell number and spreading area, cytoskeleton, focal adhesion contacts, and cell proliferation. Electrospinning using benign solvents was impossible. However, fiber mats were successfully prepared from hexafluoropropanol (HFP) solutions. Different structural morphologies and fiber diameters of the electrospun mats were observed depending on the composition and concentration of the electrospinning solutions. Both BSHC and BSHC/GAG mats supported the in vitro adhesion, growth, and differentiation of hAD-MSCs, with some variations based on their composition and structural morphology. The absence of cytotoxicity and the good hAD-MSC adhesiveness make them promising substrates for cell adhesion, proliferation, and further stem cell differentiation.